Production and Characterization of Biodiesel from Recycled wasted Cooking Oil collected from some Libyan restaurants. (Al-Farooq Journal of Sciences, 2026)
The global energy crisis and the environmental impact of fossil fuel use have accelerated the search for renewable alternatives. This study focuses on producing biodiesel from recycled used cooking oil (UCO) through transesterification using methanol and ethanol with potassium hydroxide (KOH) as a catalyst. Different concentrations of KOH (1.5%, 2.5%, and 3.5%) were tested to optimize yield and quality. Physical and chemical properties such as density, viscosity, flash point, free fatty acid content, and moisture were analyzed according to ASTM standards. The results demonstrated that sunflower oil produced the best biodiesel yield and quality, while corn oil produced satisfactory results, and palm oil exhibited poor conversion due to high free fatty acid content. Ethanol-based reactions generally yielded biodiesel with higher clarity and stability. This research confirms that recycling used cooking oil into biodiesel offers an environmentally friendly and sustainable solution to waste management and renewable energy production.
Keywords: Biodiesel; Used Cooking Oil; Transesterification; Methanol; Ethanol; Renewable Energy.